The proteomic landscape of extracellular vesicles derived from human intervertebral disc cells - Li Li; Hadil Al‐Jallad; Aiwei Sun; Miltiadis Georgiopoulos; Rakan Bokhari; Jean Ouellet; Peter Jarzem; Hosni Cherif; Lisbet Haglund (JOR Spine)
Abstract Background Extracellular vesicles (EVs) function as biomarkers and are crucial in cell communication and regulation, with therapeutic potential for intervertebral disc (IVD)‐related low back pain (LBP). EV cargo is often affected by tissue health, which may affect the therapeutic potential. There is currently limited knowledge of how the cargo of IVD cell‐derived EVs varies with tissue health and how differences in proteomic profile affect the predicted biological functions. Methods Our study purified EVs from human IVD cell conditioned media by size‐exclusion chromatography. Nanoparticle tracking analysis was conducted to measure EV size and concentration. Transmission electron microscopy and Western blot were performed to examine EV structure and markers. Tandem mass tag‐mass spectrometry was conducted to determine protein cargo. Results Most EVs were exosomes and intermediate microvesicles with an increasing amount linked to disease progression. Of the proteins detected, 88.6% were shared across the non‐degenerate, mildly‐degenerate, and degenerate samples. GO and KEGG analyses revealed that cargo from the mildly‐degenerate samples was the most distinct, with the proteins in high abundance strongly associated with extracellular matrix (ECM) organization and structure. Shared proteins, highly expressed in the non‐degenerate and degenerate samples, showed strong associations with cell adhesion, ECM–receptor interaction, and vesicle‐mediated transport, respectively. Conclusions Our findings indicate that EVs from IVD cells from tissue with different degrees of degeneration share a majority of the cargo proteins. However, the level of expression differs with degeneration grade. Cargo from the mildly‐degenerate samples exhibits the most differences. A better understanding of changes in EV cargo in the degenerative process may provide novel information related to molecular mechanisms underlying IVD degeneration and suggest new potential treatment modalities for IVD‐related LBP.